Secondary-Level Teachers’ Perceptions of Difficulties in Teaching Writing Skills in English - Kharel, Dhruba (Kanakai Journal, 2023)
The qualitative research, grounded in interpretivism, explored challenges in teaching secondary-level students writing skills in English. The study aimed to grasp English teachers’ perspectives through interviews. Challenges encompassed limited vocabulary, incorrect pronunciation, and internet dependency. Interviews with six teachers (participants) highlighted the need to address diverse learning needs and maintain a balance between grammar, composition, and creativity. Motivation proved a hurdle, influenced by internet reliance and shyness. Parents' negligence impacted students' writing habits. Additionally, poor handwriting diminished students' confidence in presenting their work- a lack of professionalism among teachers and their inadequate skills added to the challenges. Therefore, recommendations included motivating students, boosting reading practices, reducing internet dependence, and improving teacher expertise. Addressing these challenges is crucial for nurturing proficient writing skills in students.